Revolution and social justice issues in modern world - Melnikov, Adam P. (Journal of the Belarusian State University. Sociology, 2019)
The article discusses different interpretations of social justice in modern science. It pays considerable attention to the October Revolution in 1917 in Russia, as well as to various welfare state models: liberal, conservative and corporatist, socialdemocratic and socialist. The author describes the Belarusian model of welfare state, as well as gives his own definition of social justice.